2015
DOI: 10.1111/1750-3841.12838
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Including Green Tea Products for an Analytically Verified Dietary Supplement Database

Abstract: The Dietary Supplement Ingredient Database (DSID) is a federally funded, publicly accessible dietary supplement database that currently contains analytically-derived information on micronutrients in selected adult and children’s multivitamin and mineral (MVM) supplements. Other constituents in dietary supplement products such as botanicals are also of interest and thus are being considered for inclusion in the DSID. Thirty-eight constituents, mainly botanicals were identified and prioritized by a federal inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The value of this review is that it highlights the challenges researchers face in working with information on botanicals declared on DS labels and in clinical trials. As previous reviews on caffeine and green tea have demonstrated, this review again shows that the amounts of botanical or botanical constituent, form (or composition), and identity of ingredients in botanical DSs were difficult to ascertain even on labels that complied with the DS label regulations (23,24). These challenges make estimating intakes and exposures to herbs and botanicals difficult for epidemiological studies that use data solely from DS labels.…”
Section: Discussionmentioning
confidence: 68%
“…The value of this review is that it highlights the challenges researchers face in working with information on botanicals declared on DS labels and in clinical trials. As previous reviews on caffeine and green tea have demonstrated, this review again shows that the amounts of botanical or botanical constituent, form (or composition), and identity of ingredients in botanical DSs were difficult to ascertain even on labels that complied with the DS label regulations (23,24). These challenges make estimating intakes and exposures to herbs and botanicals difficult for epidemiological studies that use data solely from DS labels.…”
Section: Discussionmentioning
confidence: 68%
“…Extracts that are used in bodybuilding and weight loss have also been linked to liver injury. This has led to studies of the composition of different supplements [ 50 , 51 ]. Causes of liver toxicity from supplements appear to be due to insufficient regulatory authority, inaccurate product labeling, adulterants and inconsistent sourcing of ingredients [ 52 ].…”
Section: Challenges: Scientific Perspectivesmentioning
confidence: 99%
“…Researchers often are interested in whether a single ingredient or multiple ingredients of dietary supplements are responsible for the biological effects observed. Such questions were important in assessing the ill effects of ephedra supplements, which were banned from the market in 2004, and more recently of caffeineand green tea-containing dietary supplements and energy drinks that appeared to be associated with cardiovascular abnormalities in some users (13,17,18). Additional codes were also created in DSLD for product categories/types commonly reported in NHANES such as single vitamin and single mineral (e.g., calcium and vitamin D) product, multivitamin and mineral with botanicals, and omega-3 supplements (15).…”
Section: Descriptionmentioning
confidence: 99%